A Meta-Analysis of Prevalence and Moderating Factors of Malnutrition Among People Living With HIV Across Countries - Sukartini, Tintin; Arifin, Hidayat; Qona'ah, Arina; Mariyanti, Herdina; Kustanti, Christina Yeni; Chou, Kuei-Ru; Astuti, Trihaningsih Puji; Mafula, Dluha; Alfaruq, Muhammad Fikri; Putri, Alfiani Rahmi; Banda, Kondwani Joseph (The Journal of the Association of Nurses in AIDS Care, 2025)
Supplemental Digital Content is Available in the Text. AbstractMalnutrition is a critical issue for people living with HIV (PLWH), affecting their immune function, health outcomes, and response to antiretroviral therapy. This meta-analysis assessed the prevalence of malnutrition among PLWH and explored key moderating factors across countries. A systematic search of six databases-Cumulative Index to Nursing and Allied Health Literature, Embase, ProQuest, PubMed, Scopus, and Web of Science, included 103 studies involving 240,879 PLWH. The pooled prevalence of malnutrition was 16.6% (95% confidence interval = 14.1-19.5). Subgroup analysis revealed higher prevalence in Southeast Asia (31.1%), PLWH with primary education (37.7%), those on antiretroviral therapy for over a year (51.7%), and World Health Organization Stage 3 (36.4%). Meta-regression identified alcohol consumption, smoking, hepatitis, and tuberculosis as significant moderators. The prevalence of malnutrition among PLWH is substantial, with several moderating factors identified. Addressing malnutrition among PLWH requires routine nutritional assessments and targeted interventions to improve health outcomes and quality of life for PLWH globally.